PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN MASYARAKAT PADA KANTOR PERTANAHAN KABUPATEN KARANGANYAR - Sutarno, Sutarno (Master of Public Administration, Universitas Slamet Riyadi, 2021)
The Land Office as a public service office is also demanded to be able to always provide the best service for the society, one of them is land stewardship. This is stated in Article 14 and Article 15 of Law Number. 5 of 1960 concerning the Basic Rules of Agrarian Principles Jo, Article 33 of Law Number. 26 of 2007 concerning Spatial Planning in which spatial use refers to spatial plans implemented with land use, water use, and air use. The objective to be achieved in this study is to determine whether there is an influence of service quality on society satisfaction in the service of Land Technical Considerations (PTP) in the context of permission to change land use at the Karanganyar District Land Office.The type of this research is research with a quantitative descriptive approach. The study was conducted at the Land Office of Karanganyar Regency.The unit analysis of this study is the Land Management Section which provides services to the community related to Land Technical Considerations (PTP). This research uses simple random sampling technique. Based on data collection activities that have been carried out in March to April, the number of respondents is 50. The data used are primary data and secondary data. Data collection techniques using a questionnaire.The results of the study began with data validity using a r table comparison of 0.165 which found all valid data followed by multiple linear regression tests showed that partially reliability (reliability) had a significant effect on community satisfaction with a significance level (0,000)